Environmental degradation in sub-Saharan Africa: issues for policy analysis - Ehui, Simeon K. (International Livestock Centre for Africa, 1993)
In this paper, a broader perspective on the causes of environmental degradation is taken and issues for policy analysis are examined. Causes of natural resource degradation, property arrangements, capital markets, commodity prices, monetary policy, and marketing are discussed. Highlights issues for policy research with particular reference to macro-economic policies and property arrangements, household behaviour and resource management, valuation of resources, and productivity and sustainability measurements.